PENYELENGGARAAN PROGRAM PAUD HOLISTIC INTEGRATIF MELALUI KEMITRAAN DALAM MENINGKATKAN ASPEK PERKEMBANGAN KOGNITIF ANAK USIA DINI - Saepudin, Asep; Ardiwinata, Jajat S.; Farida, Evi (PEDAGOGIA, 2015)
This research is motivated by the still large number of agencies that do not provide early childhood services in a holistic integrative. This study used a qualitative approach with descriptive methods, data collection techniques used were interviews, observation, and documentation. The subjects were managers, tutors, learners, parents, partners and community leaders. The results of the study illustrate that: First, an overview of the implementation of integrative holistic early childhood program in early childhood education Pos Cempaka done through the stages of planning, implementation, and evaluation. Second, ECD Post Cempaka in providing integrative holistic ministry has a network of partnerships with various parties; it aims to meet the basic need of early childhood. Third, an increase in aspects of child development, this research is more focused on aspects of cognitive development because it is easier to measure the level of success it is influenced by the participation of the various parties were entwined in the partnership. Fourth, the implementation of the program .Each course there supporting factors and obstacles, as well as that occurs in early childhood Cempaka Pos. To know this researcher using SWOT analysis, strengths and opportunities that owned the Post ECD Cempaka be a supporting factor for the sustainability of the program, whileweaknesses and threats are factors that will be a matter of evaluation for managers to determine the best move for the advancement of Post ECD Cempaka.Keywords: Integrative Holistic ECD, Partnership, Aspects of Cognitive Development